Assessment of a high-level spent nuclear fuel disposal model. Issue 1 (12th September 2018) - Rodriguez-Dono, Alfonso; Olivella, Sebastia; Mokni, Nadia
Abstract : This paper assesses a model for the full-scale engineered barrier experiment (Febex) in situ test, simulating the disposal of heat-emitting, high-level spent nuclear fuel. The model has been developed using Code_Bright and is based on previous modelling efforts. The model focuses on the thermo-hydro-mechanical behaviour of a bentonite barrier surrounding a heater that simulates the heat production of radioactive spent fuel. The new model incorporates the new dismantling operations and has been compared with new in situ measurements. Once calibrated, the long-term response of the model has been analysed. Furthermore, the implementation of additional processes and their impact on hydration and stress development have been assessed. In this assessment, it has been found that the bentonite barrier does not fully saturate near the canister in any case, which is an important goal for the isolation of the spent nuclear fuel. The intrinsic permeability has been found to give results closer to measurements when its value is doubled. The double-structured model has given interesting results, but the authors found that it does not have a great influence in the general behaviour of the model.